1993
DOI: 10.1016/0014-5793(93)80078-9
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol esters induce nitric oxide synthase and increase arginine influx in cultured peritoneal macrophages

Abstract: Incubation of peritoneal macrophages with /3-phorbol 12,13-dibutyrate promotes a time-dependent release of NO to the incubation medium. This effect was antagonized by LPS, a well known inducer of nitric oxide synthase (NOS) expression in macrophages, and was inhibited by .V"-methylt_-arginine and N"-nitro-L-arginine. An increase in intracellular cGMP and NOS activity was observed in parallel with NO release. The induction of NOS was accompanied by a stimulation of arginine influx within the cell. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
3

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 27 publications
(16 reference statements)
7
54
3
Order By: Relevance
“…This hypothesis is substantiated by our current findings, which demonstrate that, unlike LPS and IFN-γ-induction of NO synthesis, induction of -arginine transport is largely independent of PTKs. This process is also independent of PKC activation and contrasts with observations in rat peritoneal macrophages [29], human umbilical vein endothelial cells [30] and the human intestinal epithelial cell line Caco-2 [31], where PKC has been implicated as the key signalling mechanism mediating enhanced -arginine transport. Although there are cell, and maybe species, differences, it is worth noting that, in some of the studies mentioned above, PKC was implicated simply on results obtained with PKC activators including PMA, or on the use of relatively high concentrations of PKC inhibitors, which may not only be non-selective but also cytotoxic.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…This hypothesis is substantiated by our current findings, which demonstrate that, unlike LPS and IFN-γ-induction of NO synthesis, induction of -arginine transport is largely independent of PTKs. This process is also independent of PKC activation and contrasts with observations in rat peritoneal macrophages [29], human umbilical vein endothelial cells [30] and the human intestinal epithelial cell line Caco-2 [31], where PKC has been implicated as the key signalling mechanism mediating enhanced -arginine transport. Although there are cell, and maybe species, differences, it is worth noting that, in some of the studies mentioned above, PKC was implicated simply on results obtained with PKC activators including PMA, or on the use of relatively high concentrations of PKC inhibitors, which may not only be non-selective but also cytotoxic.…”
Section: Discussioncontrasting
confidence: 89%
“…As with iNOS, the role of either PTK or PKC in enhanced -arginine transport induced by pro-inflammatory mediators remains inconclusive. Limited reports have suggested that exposure to phorbol esters enhances -arginine entry into rat peritoneal macrophages [29], human umbilical vein endothelial cells [30] and the human intestinal epithelial cell line Caco-2 [31]. However, Schmidlin and Wiesinger [7] failed to modulate arginine transport in activated astrocytes using the PKC inhibitor staurosporine.…”
Section: Introductionmentioning
confidence: 99%
“…1). Contrary to this behavior and in agreement with previous work (13,14), stimulation of primary cultures of rat peritoneal macrophages or isolated hepatocytes with PDBu produced a NO x Ϫ release that was 83 and 71%, respectively, of the response elicited after LPS treatment. This PDBu-dependent NO x Ϫ synthesis was absent in other cells such as isolated splenocytes, B cells, or human neutrophils.…”
Section: Methodssupporting
confidence: 92%
“…The cells were cultured in RPMI 1640 medium supplemented with 2 mM glutamine, 10% FCS, and antibiotics (50 g/ml of penicillin, streptomycin, and gentamicin). Peritoneal macrophages were obtained from Swiss mice following a published method (13). Rat hepatocytes, murine splenocytes and B cells, and human neutrophils were isolated and purified as described previously (14,26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation